Research and publications in Islamic perspective (part 4: publications) - Khedher, Akram M Z M (Kulliyyah of Information and Communication Technology, IIUM, 2023)
This article is the 4th part in the series of the “Research and Publications in Islamic Perspective”, while part 1 was about the introductory on this topic, part 2 was focusing on experimental results of the research, and part 3 discussed the presentation issues which is needed in any research, in this article (part 4) we are going to discuss the publication of the results & finding of any research and the important of this matter from Islamic perspective.